DESIGN AND DEVELOPMENT OF A PULSE GENERATOR SYSTEM FOR THE FORMATION AND CHARACTERIZATION OF Ni-TiN/Si3N4 COMPOSITE LAYERS USING PULSE CURRENT DENSITY ELECTRODEPOSITION METHOD: RANCANG BANGUN SISTEM PULSE GENERATOR UNTUK PEMBENTUKAN DAN KARAKTERISASI LAPISAN KOMPOSIT Ni-TiN/Si3N4 DENGAN METODE ELEKTRODEPOSISI RAPAT ARUS PULSA - Arsyan Fadilah; Esmar Budi; Teguh Budi Prayitno (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
This research aims to make a pulse generator system and test the design results in the electrodeposition process by analyzing the composition and surface morphology of the Ni-TiN/Si3N4 composite layer formed. The Ni-TiN/Si3N4 coating is used because it can increase hardness, seal diffusion to the substrate, and prevent oxidation at high temperatures. Tungsten carbide (WC) is coated to reduce wear, improve the surface, increase adhesion, and strength of the substrate without changing the original properties. Pulse current electrodeposition uses Pulse Width Modulation (PWM) circuit with IC 555 as pulse generator. The result of the Pulse Generator system design is a pulse wave that can be adjusted by adjusting the duty cycle value using a potentiometer and can be observed using an oscilloscope, and the pulse height or output current can be adjusted as needed and can be measured using a multimeter. The electrodeposition process was carried out for 30 minutes at 40ºC with a stirring rate of 600 rpm. Morphological scanning using a Scanning Electron Microscope (SEM) showed a rough surface, uneven particle size distribution, and agglomeration in the formed layer. Energy Dispersive Spectroscopy (EDS) scanning results showed the success of the coating formed with the presence of Ni, TiN, and Si3N4 metal elements with a thickness of 2.7191 μm.